ETMR-06. Molecular and clinical characteristics of CNS tumors withBCOR(L1) fusion/internal tandem duplication. (3rd June 2022) - Gojo, Johannes; Schmitt-Hoffner, Felix; Mauermann, Monika; von Hoff, Katja; Sill, Martin; Korshunov, Andrey; Stichel, Damian; Capper, David; Tauziede-Espariat, Arnault; Varlet, Pascale; Aldape, Kenneth; Abdullaev, Zied; et al.
Abstract: Central nervous system (CNS) tumor with BCOR internal tandem duplication ( BCOR -ITD) have recently been introduced in the 5th edition of the WHO classification of CNS tumors, however, their molecular makeup and clinical characteristics remain widely enigmatic. This is further complicated by the recent discovery of tumors characterized by gene fusions involving BCOR or its homologue BCORL1 . We identified a cohort of 206 BCOR altered CNS tumors via DNA methylation profiling and conducted in-depth molecular and clinical characterization in an international effort. By performing t-SNE clustering analysis we found that BCOR -fusion tumors form a distinct cluster (n=61), adjacent to BCOR -ITD cases (n=145). The identified fusion partners of BCOR(L1 ) included EP300 (n=20), CREBBP (n=5), and NUTM2HP (n=1). Notably, three cases within the BCOR -ITD cluster harbored a c-terminal intragenic deletion within BCOR . With respect to clinical characteristics gender ratio was balanced in BCOR -fusion cases (m/f, 1.1), whereas predominance of male patients was observed in the BCOR -ITD group (m/f, 1.5). Moreover, age at diagnosis of BCOR -fusion patients was higher as compared to BCOR -ITD cases (15 vs 4.5 years). Interestingly, BCOR -fusion tumors were exclusively found in the supratentorial region being originally diagnosed as ependymomas or gliomas whereas BCOR -ITD emerged across the entire CNS with diverse original diagnoses. 8% of BCOR -ITD and none of BCOR -fusion cases were disseminated at diagnosis. In line with this observation, 40% of first relapses within the BCOR -ITD group were metastatic which was less frequent in BCOR -fusion tumors. Survival estimates demonstrated no differences, generally showing short median PFS ( BCOR -fusion, 2 years, n=15; BCOR -ITD, 1.8 years, n=55) and intermediate OS rates ( BCOR -fusion, 6.8 years, n=18; BCOR -ITD 6.3 years, n=60). Further molecular and clinical characterization is ongoing potentially revealing first therapeutic leads for these highly aggressive CNS tumor types.